MPROVING THE MECHANISM OF INCREASING THE ECONOMIC POWER OF INDUSTRIAL ENTERPRISES ON THE BASE OF ECONOMETRIC MODELS (Scientific Journal of Actuarial Finance and Accounting, 2024)
Production processes in industrial enterprises are expressed on the basis of simulation models. Techniques are expressed and proposed that allow showing the general characteristics of the entire system through a model based on a system-integrated approach, that is, by reaching the p-level in determining the economic power efficiency indicator. calculation model and scheme describing the production capacity of industrial enterprises.